2019
DOI: 10.1113/jp277190
|View full text |Cite
|
Sign up to set email alerts
|

Carotid chemoreflex activity restrains post‐exercise cardiac autonomic control in healthy humans and in patients with pulmonary arterial hypertension

Abstract: Key pointsr Dysfunction of post-exercise cardiac autonomic control is associated with increased mortality risk in healthy adults and in patients with cardiorespiratory diseases.r The afferent mechanisms that regulate the post-exercise cardiac autonomic control remain unclear.r We found that afferent signals from carotid chemoreceptors restrain the post-exercise cardiac autonomic control in healthy adults and patients with pulmonary arterial hypertension (PAH).r Patients with PAH had higher carotid chemoreflex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 52 publications
(103 reference statements)
1
9
0
1
Order By: Relevance
“…Another study, conducted in healthy humans, showed that the normalV˙E response to transient hypoxia at rest did not vary from pre‐ to post‐heavy‐intensity exercise (Clement et al, ), indicating therefore that the carotid chemoreflex sensitivity was unchanged. Together, data from our and previous studies (Clement et al, ; Paula‐Ribeiro et al, ) support that carotid chemoreceptors, per se, do not seem to contribute at all or contribute to a small part of the normalV˙E recovery from exercise.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Another study, conducted in healthy humans, showed that the normalV˙E response to transient hypoxia at rest did not vary from pre‐ to post‐heavy‐intensity exercise (Clement et al, ), indicating therefore that the carotid chemoreflex sensitivity was unchanged. Together, data from our and previous studies (Clement et al, ; Paula‐Ribeiro et al, ) support that carotid chemoreceptors, per se, do not seem to contribute at all or contribute to a small part of the normalV˙E recovery from exercise.…”
Section: Discussionsupporting
confidence: 81%
“…A study in patients with right‐sided heart failure induced by pulmonary arterial hypertension employed a similar methodological approach to ours (Paula‐Ribeiro et al, ). One hundred percent O 2 was given in the inspired air 10 s before the onset of active recovery from incremental exercise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased vagal modulation in acute saturated environments has been attributed to both elevated O 2 and increased pressure (independent of O 2 ) ( Lund et al, 1999 ). Mechanisms for this vagal responsiveness have been ascribed to vagal outflow compensating for O 2 and/or pressure induced vasoconstriction (baroreflex), increased cardiac efficiency due to elevated PPO 2 exposure in cardiac tissue, prolonged Q-T interval, and/or carotid chemoreflex inhibition ( Demchenko et al, 2013 ; Paula-Ribeiro et al, 2019 ; Goyal et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…As such, brain hypoxia sensors can modulate the neurovascular coupling to regional cerebral deoxygenation via astrocytes and pericytes, which in turn stimulate the brain stem neuronal respiratory network resulting in hyperventilation. Secondly, both peripheral and central chemoreceptors overactivity in PAH (Malenfant et al, 2017; Paula‐Ribeiro et al, 2019; Vicenzi et al, 2016) might stimulate ventilation in an additive manner. Smith et al demonstrated an hyperadditive two to fourfold response change in the central chemoreceptor response to carotid chemoreceptors hypersensitivity, resulting in further increase in ventilation in awaked dogs (Smith, Blain, Henderson, & Dempsey, 2015).…”
Section: Discussionmentioning
confidence: 99%